Uso de cenizas volantes provenientes de calderos de lecho fluidizado en concretos autocompactantes y su influencia en la resistencia a la compresión. - Balcázar Cabello, Antonio (2014)
This research's main contribution to minimize environmental pollution using fly ash are residues from the combustion of coal fluidized bed boilers, which damage the environment and health; and also contribute with new knowledge in the development of the construction industry. This research was conducted testing compressive strength of 36 specimens according to ASTM C-39, developed under the design of self-compacting concrete with replacement levels of portland cement by fly ash: 0%, 10%, 20% and 30% by weight of mixture, and wherein the dosages of superplasticizer used Viscocrete 1110 Sika brand of 1.1%, 1.40%, 1.75% and 2.12%, respectively, which improve the workability of the mixture, but without influencing the compressive strength. The design has a water / cement weight ratio of 0.44, with a base of 40 MPa. The samples were subjected to the test of resistance to compression at 14, 28 and 90 days of curing. The results at 14 and 28 days of curing, and fly ash replacement for portland cement 10%, exceeds the value of the compressive strength at 12% and 3% respectively, in the standard sample. However at 90 days of curing, the strength of the specimen with a replacement level of 10% fly ash is second pattern in 11%. All specimens cured at 90 days above 40 MPa design strength, and comes to the conclusion that you can use a percentage of substitution of fly ash 10% higher initial resistance; while substitutions with 20% and 30% for resistors long cure times. The adhesion test showed that the greater the replacement of Portland cement by fly ash is a significant reduction in adhesion. The presences of unburned carbon in the fly ash affect the compressive strength and adherence of the concrete specimens. Additionally, the absorption test was done to determine the degree of porosity and know how durable our specimens are. It was observed that the degree of porosity is inversely proportional to the compression strength.